Accelerated fermentation of Idli batter using Eleusine coracana and Pennisetum glaucum - Chelliah, Ramachandran (J Food Sci Technol, 2017)
The present study focuses on reduction in fermentation time of idli batter and its enrichment with calcium and iron using finger millet and pearl millet. Fermentation time decreased from 12 to 6 h with addition of finger millet and to 8 h with pearl millet. Rate of fermentation, bulk density, viscosity, microbial changes and particle morphology were assessed in the batter; nutritional quality, sensory, phytochemicals and internal characteristics of idli were investigated. The color and texture characteristics of both batter and idli were evaluated. The pH and titratable acidity of control batter at 6 h was 5.32 and 0.27%, addition of finger and pearl millet changed to 4.32, 0.45% and 4.53, 0.45% at respective fermentation times (6 and 8 h). The viable yeast, lactic acid bacteria and total bacterial count (log CFU g(−1)) in the batters increased with time, reaching 1.26, 3.85, 4.56 (control); 2.32, 9.84, 9.58 (finger millet) and 1.76, 7.34, 7.74 (pearl millet) respectively at the end of 6 h of fermentation. Addition of finger millet and pearl millet flour (10% w/w) to the batter enhanced the dietary fiber by 28 and 23%, calcium by 113 and 56%, iron by 51 and 258% in the respective idlies when compared with the control.